Cm-Length free-standing Fe3C-filled thin graphite-like films and buckypaper-like films with high smoothness. Issue 102 (20th October 2016) - Guo, Jian; Lan, Mu; He, Yi; Hou, Yidong; Zhang, Xi; Zhang, Sijie; Wang, Shanling; Xiang, Gang; Boi, Filippo S.
Abstract : We report the fabrication of cm-length smooth graphitic-films filled with Fe3 C particles and of cm-length smooth buckypaper-like films comprising thin walled carbon nanotubes filled with Fe3 C nanowires with reflectance in the 450–1000 nm region. Abstract : We report the fabrication of cm-length free standing thin graphitic-films filled with Fe3 C particles and of cm-length free standing thin buckypaper-like films comprising thin walled carbon nanotubes filled with Fe3 C nanowires which exhibit a high smoothness with an unusual reflectance in the 450–1000 nm wavelength region. These films are fabricated by chemical vapour deposition of ferrocene in presence of large quantities of toluene or dichlorobenzene respectively. The structural, magnetic and optical properties of these films are analysed in detail through scanning and transmission electron microscopy, X-ray diffraction, Raman spectroscopy, vibrating sample magnetometry and spectrography.